Study of digitizer properties in nuclear spectroscopy experiments - Liapatis, A.; Axiotis, M. (HNPS Advances in Nuclear Physics, 2022)
In the present work a new CAEN 725S digitizer was implemented and compared to standard analog electronics in simple detector circuits, widely used in experimental nuclear physics. The first obtained results demonstrated that low-cost digital signal processing can offer a faster, improved performance regarding dead time corrections, without any significant effect in the obtained detector resolution values.